To educate for the happiness: challenge of the today teacher - Schiappa Pietra, Claudia (2018)
One of the goals of the parents and educators look and want for the next generations is to educate them for the happiness and moreover in this age in which the technology and the science have displacing the human being; relegating the family, the religion, the values and feelings for criteria of functionality and profitability. We are attending an increasing number of children who scarcely can experience positive, such emotions as the curiosity, the interest or the happiness.Educating for the happiness is to prepare future generations for the future, that does not mean to give them all easily or make them people capricious or without limits. The educator must orient his work by educating for the true happiness and that means, to bring the students to the goodness, the high and dignified values so that they can develop with autonomy and initiative and to be able to decide their own project of life, trying to get the best out of the students, guiding into the right direction of life.  The present article expects to give a general vision of some contributions that the positive psychology, it realizes to the education in order to help with the teachers  to educate for the happiness. The happiness is learned at home and is reinforced in the school; for it, the Pope Francisco says to us what the family is, the place where the happiness is forged by means of the harmony between its members because really they love each other. He advises three words: pardon, thank you and pardon.